Influencing factors of serum magnesium in CKD5 patients: A multicenter study in southern China - Wang, Jiali; Lin, Shujun; Li, Hong-Yan; Tang, Wenzhuang; Liu, Yiping; Zhou, Tianbiao (Frontiers in Public Health, 2022)
Introduction Magnesium (Mg) disturbances are related to cardiac, bone, and renal patient mortality. In this study, we compared biochemical markers in hemodialysis (HD) and peritoneal dialysis (PD) patients and explored the influencing factors of serum Mg in stage 5 chronic kidney disease (CKD5) patients. Material and methods All 598 patients with CKD5 from three medical centers in South China were recruited into this prospective cohort study from March 1, 2018, to January 31, 2021. Our study recorded the clinical characteristics and laboratory data of the patients. Results Hemodialysis patients (0.99 ± 0.19 mmol/L) had a higher mean serum Mg level than PD patients (0.86 ± 0.20 mmol/L; p < 0.01). Regression analysis showed that only corrected calcium (Ca), phosphate (P), Ca/Mg, Ca × P, albumin (Alb), total protein and creatine (Cr) predicted Mg levels in CKD5 patients (p < 0.01). Ca/Mg predicts hypomagnesemia with 78% sensitivity and 85% specificity in CKD5 patients. The AUC value corresponding to Ca/Mg was 0.88. Conclusions This multicenter study in southern China showed that for all CKD5 patients, corrected Ca and Alb had a significant positive effect on serum Mg, while Ca/Mg had a significant negative effect on serum Mg. In 123 HD patients, Ca × P was positively associated with Mg while Ca/Mg and P were negatively associated with Mg. In 398 PD patients, Ca × P, Alb, and total protein were positively associated with Mg while Ca/Mg and P were negatively associated with Mg. In 77 non-dialysis patients, corrected Ca, Cr, and total protein were positively associated with Mg while Ca/Mg was negatively associated with Mg. Furthermore, Ca/Mg might be another useful technique to monitor blood Mg levels in CKD5 patients. Clinical trial registration ChiCTR1800014557.